Producción cacaotera de las fincas del sitio Valle Hermoso de la parroquia Bella María del cantón Santa Rosa. - Martínez Molina, Keiko Mariuxi (2015)
The Valle Hermoso site Bella Maria parish in the canton Santa Rosa is a purely commercial sector, for any reason, is considered highly feasible to create a marketing producer of cocoa plants. The work is developed by chapters of the whole thesis, the problem causes, effects, objectives, define, formulation and justification is minutely detailed, a little blurb story about this business is stable, plus all the necessary information was found for better understanding of the legwork finding their respective assumptions and variables.